Indonesia Economic Quarterly, December 2010 : Maximizing Opportunities, Managing Risks - World Bank (Jakarta, 2017)
The Indonesian economic quarterly reports on and synthesizes the past three months' key developments in Indonesia's economy. Its coverage ranges from the macro economy to financial markets to indicators of human welfare and development. It is intended for a wide audience, including policy makers, business leaders, and financial market participants, and the community of analysts and professionals engaged in Indonesia's evolving economy. The challenge for Indonesia is to maximize the opportunities that this brings, in terms of enhancing future growth and making investments that can improve the welfare of the entire population, while managing the associated risks. Strong capital inflows, particularly portfolio, have been seen across emerging markets, including Indonesia. These inflows are driven by yield differentials and the stronger growth prospects, and improved creditworthiness, of emerging economies relative to heavily indebted, higher-income economies. Further quantitative easing in the US has provided an additional, cyclical boost to this trend. Global commodity prices also picked up in recent months. In November, the US dollar price of non-energy commodities rose by 3.4 percent over the month with food and raw material prices up by 4.9 percent and 7.6 percent, respectively. The underlying drivers were strong growth in demand from emerging economies, particularly China, and also supply disruptions in the agriculture sector.